Local communities’ preferences and willingness to pay for improving tourist facilities and conservation of ecosystem in Arugambay lagoon, Sri Lanka - Misfa, S.L.F.; Sivashankar, S.; Sooriyakumar, K.; Sarujan, S. (Wayamba University of Sri Lanka, 2025)
Arugam Bay lagoon holds an economic and ecological value and supports tourism and biodiversity. This study used the choice experiment approach to investigate the local communities' preferences and willingness to pay for tourism development and improvement in the Arugam Bay lagoon ecosystem. The following attributes were considered in this study: safari facilities, wildlife protection, mangrove restoration, and payment. A random sampling approach was employed, and 350 questionnaires were collected from local communities. The Random Parameter Logit (RPL) model was used to account for preference heterogeneity among the respondents. The results show that respondents prefer and are willing to pay LKR 2493.87 to improve the safari facilities in the area. Also, they are willing to pay LKR 1782.36 and LKR 1438.07 to increase the mangroves by 25% and 50%, respectively. They also like to pay LKR 413.09 for wildlife protection. Further, results indicate that respondents with an education level of grade 11 and above are willing to choose alternatives with improved levels rather than the status quo. These findings will help policymakers and local authorities design appropriate policies that will boost the country's economy by improving tourist facilities.
Keywords: Choice experiment; Random parameter logit model; Tourism; Willingness to pay